2012
DOI: 10.4172/2155-9864.s1-004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Administration of Fibrinogen is Associated with Increased Risk of Postoperative Thromboembolic Complications after Cardiac Surgery

Abstract: Introduction: Fibrinogen is a key protein in achieving and maintaining haemostasis. Prophylactic fibrinogen has been shown to reduce bleeding after coronary artery bypass graft (CABG) and studies have reported an inverse correlation between preoperative plasma concentration of fibrinogen and the volume of postoperative bleeding after CABG. This indicates that preoperative fibrinogen plasma concentration, even within the normal range, is a limiting factor for haemostasis after cardiac surgery. In theory, fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In contrast to these two studies, Jakobsen et al found that perioperative fibrinogen administration was an independent risk factor for postoperative stroke and renal failure in a cohort of 1,876 patients, of whom 168 patients received fibrinogen concentrate (9.6%). 12 The present study, which is markedly larger than the previous ones (n ¼ 5,408, of which 564 were treated with fibrinogen [10.4%]), confirms the results of Fassl and Maeda's studies, 10,11 that is , no significant differences in thromboembolic events or mortality were observed between patients who did or did not receive fibrinogen concentrate perioperatively. The conflicting results in Jakobsen's study 12 may largely be explained by the statistical approach; the results in that study were neither adjusted for excessive bleeding nor transfusion requirements, which was the case in the present study and in the study by Fassl.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to these two studies, Jakobsen et al found that perioperative fibrinogen administration was an independent risk factor for postoperative stroke and renal failure in a cohort of 1,876 patients, of whom 168 patients received fibrinogen concentrate (9.6%). 12 The present study, which is markedly larger than the previous ones (n ¼ 5,408, of which 564 were treated with fibrinogen [10.4%]), confirms the results of Fassl and Maeda's studies, 10,11 that is , no significant differences in thromboembolic events or mortality were observed between patients who did or did not receive fibrinogen concentrate perioperatively. The conflicting results in Jakobsen's study 12 may largely be explained by the statistical approach; the results in that study were neither adjusted for excessive bleeding nor transfusion requirements, which was the case in the present study and in the study by Fassl.…”
Section: Discussionsupporting
confidence: 89%
“…A larger proportion of patients who received fibrinogen concentrate were transfused with RBCs (77.9 vs. 40.9%), plasma (61.5 vs. 13.8%), platelets (57.8 vs. 10.2%) and any transfusion of blood products (83.1 vs. 42.7%) (all p < 0.001). The median transfused volumes were higher in patients who received fibrinogen concentrate for any transfusion (8 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Patients who had a thrombotic event or died during follow-up were older, more often women, had higher Euroscore, significantly higher incidence of previous stroke and diabetes, higher fibrinogen concentration, lower haemoglobin concentration, inferior renal function, underwent more complex surgical procedures and received more blood transfusions (►Supplementary Tables S3 and S4 [available in the online version]).…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation